Psychiatric disorders in childhood cancer survivors in Denmark, Finland, and Sweden: a register-based cohort study from the SALiCCS research programme. (January 2022) - Frederiksen, Line Elmerdahl; Erdmann, Friederike; Mader, Luzius; Mogensen, Hanna; Pedersen, Camilla; Kenborg, Line; Bautz, Andrea; Talbäck, Mats; Hirvonen, Elli; Nielsen, Thomas Tjørnelund; Andersen, Elisabeth Anne Wreford; Holmqvist, Anna Sällfors; et al.
Summary: Background: A childhood cancer diagnosis and treatment-induced somatic late effects can affect the long-term mental health of survivors. We aimed to explore whether childhood cancer survivors are at higher risk of psychiatric disorders later in life than their siblings and the general population. Methods: In this register-based cohort study (part of the Socioeconomic Consequences in Adult Life after Childhood Cancer [SALiCCS] research programme), we included 5-year survivors of childhood cancer diagnosed before 20 years of age between Jan 1, 1974 and Dec 31, 2011, in Denmark, Finland, and Sweden. In Denmark and Sweden, 94·7% of individuals were born in a Nordic country (ie, Denmark, Finland, Iceland, Norway, or Sweden); similar information was not available in Finland. Data on ethnicity were not collected. Survivors were compared with their siblings and randomly selected individuals from the general population who were matched to the survivors by year of birth, sex, and geographical region. We followed up our study population from 5 years after the childhood cancer diagnosis or corresponding calendar date for matched individuals (the index date) until Aug 11, 2017, and assessed information on hospital contacts for any and specific psychiatric disorders. For siblings, the index date was defined as 5 years from the date on which they were of the same age as their sibling survivor when diagnosed with cancer. Findings: The study population included 18 621 childhood cancer survivors (9934 [53·3%] males and 8687 [46·7%] females), 24 775 siblings (12 594 [50·8%] males and 12 181 [49·2%] females), and 88 630 matched individuals (47 300 [53·4%] males and 41 330 [46·6%] females). The cumulative incidence proportion of having had a psychiatric hospital contact by 30 years of age between Jan 1, 1979, and Aug 11, 2017, was 15·9% (95% CI 15·3–16·5) for childhood cancer survivors, 14·0% (13·5–14·5) for siblings, and 12·7% (12·4–12·9) for matched individuals. Despite a small absolute difference, survivors were at higher relative risk of any psychiatric hospital contact than their siblings (1·39, 1·31–1·48) and matched individuals (hazard ratio 1·34, 95% CI 1·28–1·39). The higher risk persisted at the age of 50 years. Survivors had a higher burden of recurrent psychiatric hospital contacts and had more hospital contacts for different psychiatric disorders than their siblings and the matched individuals. Interpretation: Childhood cancer survivors are at higher long-term risk of psychiatric disorders than their siblings and matched individuals from the general population. To improve mental health and the overall quality of life after childhood cancer, survivorship care should include a focus on early signs of mental health problems, especially among high-risk groups of survivors. Funding: NordForsk, Aarhus University, Swedish Childhood Cancer Foundation, Danish Health Foundation, and Swiss National Science Foundation.